Zithromax Z-Pak and the Biaxin BBQ (A) - Hennessy, Julie, (SAGE Knowledge. Cases., 2017)
The Biaxin case deals with competition in the mature market for antibiotics designed for use in the treatment of bacterial respiratory infections. The case tells the story of how Pfizers Zithromax stole the share dominance of an established brand, Abbotts Biaxin. The case deals with the importance in pharma markets of consumer (patient) and channel (physician and insurance payer) insight as well as pharmacological efficacy data.